Conflict Resolution of Political Parties in The Coalition Nominating Presidential/Vice Presidential Candidates in Indonesia in 2024 - Unggul Sugi Harto; Diniyanto, Ayon; Baqil, Youssef; Death, Carl H; Muyassaroh, Inas Sany (Jurnal Studi Pemerintahan, 2026)
This research investigates the friction and subsequent settlement strategies within party alliances during the 2024 Indonesian presidential election. By examining high-level negotiations and the shifting landscape of candidate nominations, the study interprets these dynamics as essential conflict management within a multiparty framework. Using a qualitative lens, the author analyzed digital media reports through thematic coding to pinpoint how alliances were formed, broken, and rebuilt. The analysis reveals that tension primarily stemmed from a "bottleneck" of available candidates compared to the vast ambitions of party elites. Interestingly, when deadlocks occurred, parties did not simply compromise; they either dissolved the partnership entirely or executed a "strategic pivot" to more promising camps. This fluid movement eventually distilled the political field into three primary blocs: the PDIP-centered axis supporting Ganjar Pranowo, the Prabowo Subianto coalition, and the Anies Baswedan alliance. Ultimately, the study concludes that Indonesian coalitions are defined by pragmatic survival rather than shared ideology, serving as elastic tools for managing elite competition in a modern democracy.